LncTUG1 ameliorates renal tubular fibrosis in experimental diabetic nephropathy through the miR-145-5p/dual-specificity phosphatase 6 axis - Wang, Taoxia; Cui, Shubei; Liu, Xiaoli; Han, Li; Duan, Xiaoting; Feng, Shuning; Zhang, Sen; Li, Guiying (Renal failure, 2023)
The renal interstitial fibrosis contributes to the progression and deterioration of diabetic nephropathy (DN). Long noncoding RNA taurine-up-regulated gene 1 (TUG1) in kidneys may be down-regulated by hyperglycemia. We aim to explore its role in tubular fibrosis caused by high glucose and the possible target genes of TUG1. In this study, a streptozocin-induced accelerated DN mouse model and a high glucose-stimulated HK-2 cells model was established to evaluate TUG1 expression. Potential targets of TUG1 were analyzed by online tools and confirmed by luciferase assay. A rescue experiment and gene silencing assay were used to investigate whether TUG1 plays its regulation role via miR-145-5p/dual-specificity phosphatase 6 (DUSP6) in HK2 cells. The effects of TUG1 on inflammation and fibrosis in high glucose treated tubular cells were evaluated by in vitro study, as well as in vivo DN mice model through AAV-TUG1 delivery. Results showed TUG1was downregulated in HK2 cells incubated with high glucose while miR-145-5p was upregulated. Overexpression of TUG1 alleviated renal injury by suppressing inflammation and fibrosis in vivo. Overexpression of TUG1 inhibited HK-2 cell fibrosis and relieved the inflammation. A mechanism study demonstrated that TUG1 directly sponged to miR-145-5p, and DUSP6 was identified as a target downstream of miR-145-5p. In addition, miR-145-5 overexpression and DUSP6 inhibition countervailed the impacts of TUG1. Our findings revealed that TUG1 overexpression alleviates kidney injury in DN mice and decreases the inflammatory response and fibrosis of high glucose-stimulated HK-2 cells via miR-145-5p/DUSP6 axis.